Multiweighted Analysis (MWA): Environmental Aspects in CommunityEmpowerment - Fadilah, Sri; ., Nurleli; Rosdiana, Yuni; Nurcholisah, Kania; Maemunah, Mey; Fitriah, Epi (KnE Social Sciences, 2023)
One of the impacts of the pandemic on zakat institutions is the occurrence of a very significant change in the zakat intermediation program, including in the assessment of the (community empowerment program performance) that is funded by zakat funds. There are three aspects that become the indicators of community empowerment performance, namely; social, economic, and environmental aspects. In this article, the authors give their assessment of the performance of community empowerment based on environmental aspects. It is followed by an assessment of community empowerment performance using multiweighted analysis (MWA). The goal of this research is to evaluate the performance of a community empowerment program from the environmental aspect with MWA. The research method used is a case study method with a descriptive analysis approach. Data collection techniques used were documentation and interviews. The result of the research is the weight for the environmental dimension and shows the performance of community empowerment is good and can be received as the standard of performance for community empowerment environment dimension. Keywords: environment, multiweighted analysis, empowerment